Parafilia wyzwaniem dla małżeństwa kanonicznego - Szymańska, Kinga (Ius Matrimoniale, 2020)
The considerations made in this article justify the conclusion that a paraphilic assesses the marriage from a selfish perspective, because everything he does is aimed at satisfying his pleasure. He does not consider the other person or the possibility of treating him objectively - in other words, a parafilik treats his partner as a thing to satisfy his selfish need for pleasure. Meanwhile, in the marriage relationship, closeness and realization of the good of the other party are sought as an equal partner. On the other hand, paraphilism, which is a sexual impulse, destroys not only the marriage but the spouse and, to a greater or lesser extent, the paraphilic himself. In a marriage with a paraphilic, there is no stability, no realization of the spouse's good, no realization of the community of life and love, only instinctive satisfaction, which is also unnatural. Nevertheless, regardless of the definition of paraphilia in medical sciences and psychology, when conducting a trial in an ecclesiastical court, it should be verified in the light of the concept of Christian anthropology, proper to canon studies. The paraphilia itself does not nullity it, it all depends on the severity of the disorder in question and its impact on the functioning in marriage.